2005
DOI: 10.1143/jjap.44.3643
|View full text |Cite
|
Sign up to set email alerts
|

Write-Once Disc with BiFeO Thin Films for Multilevel Optical Recording

Abstract: We optimized BiFeO thin film for use in multilevel optical recording. Due to minimal intersymbol interference (ISI), we obtained a 2.57% sigma-to-dynamic range (SDR) at a recording capacity of 25 GB. We confirmed that our write-once disc achieved a recording capacity of 25 GB using a laser diode with a 405-nm wavelength and a 0.65-numerical aperture objective lens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…6 Inorganic-type materials include phase-change alloys, 7 single-layer AlSi alloys, 8 bilayer metals such as Cu/ Si, 9 Zn/ Ge, 10 Ge/ Au, 11 Cu/ a-Si, 12 etc. Among these, Bi-related alloys such as Bi-Ge alloy 13,14 and Bi oxide ͑BiFeO͒ 15,16 exhibit promising applications for write-once data storage. For Bi-Ge-͑N͒ alloy, the recording mechanism was attributed to the reflectivity change caused by the decomposition of Bi nitride in the recording layer as well as the deformation in recording marks due to the gas release.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Inorganic-type materials include phase-change alloys, 7 single-layer AlSi alloys, 8 bilayer metals such as Cu/ Si, 9 Zn/ Ge, 10 Ge/ Au, 11 Cu/ a-Si, 12 etc. Among these, Bi-related alloys such as Bi-Ge alloy 13,14 and Bi oxide ͑BiFeO͒ 15,16 exhibit promising applications for write-once data storage. For Bi-Ge-͑N͒ alloy, the recording mechanism was attributed to the reflectivity change caused by the decomposition of Bi nitride in the recording layer as well as the deformation in recording marks due to the gas release.…”
mentioning
confidence: 99%
“…14 As to the BiFeO, the signal recording was resulted from the crystallization of Bi and BiO. 16 This work studies the feasibility of Bi-Fe-͑N͒ recording layer to HD DVD recordable ͑DVD-R͒ optical disks and the recording mechanism. Optical disk samples were prepared in accord with HD-DVD specifications 17 via sputtering process.…”
mentioning
confidence: 99%
“…There are many reasons which cause high parasitic current; however, the primary cause is a high amount of impurities during the deposition process, and the chemistry of the BFO unit. One potential defect is related to the evaporation of bismuth during the preparation process, thus changing the chemical valence of Fe +2 to Fe +3 [11,12] ions due to the evaporated Bi +2 [11,12] cations and oxygen vacancies. Uncompensated vacancies lead to a distribution of spin moment of the entire cell unit.…”
Section: Structural Characterization Of Bfo Materialsmentioning
confidence: 99%
“…At present, recording materials compatible with blue-laser recording are of particular interest. For such materials, organic ones are dyes that are sensitive to blue irradiation while inorganic ones include phase-change-based alloys, 5,6) AgInSbTe-SiO 2 nanocomposite films, 7,8) single layer metals such as AlSi alloys, 9,10) bismuth oxide (BiFeO) [11][12][13] and Bi-Fe-(N) layer, 14) and bilayer metals such as Ge/Au, [15][16][17][18] Cu/Si, 19) ZnO/Ge, 20) amorphous silicon (a-Si)/Cu, [21][22][23][24] a-Si/Al, 24,25) a-Si/Ni, [26][27][28] and Bi/Ge. 29,30) In our previous study, 14) the Bi-Fe-(N) system was demonstrated to be a promising medium for high-density write-once recording.…”
Section: Introductionmentioning
confidence: 99%